2017
DOI: 10.1111/ijlh.12755
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of sample preparation for flow cytometry

Abstract: We suggest to use LWSW method also at diagnosis to obtain more comparable antibody intensity expressions when samples from the same patient are processed for MRD evaluation after bulk lysis. Moreover, LWSW can prevent nonspecific bindings, shows no differences in the identification and quantitation of the populations of interest, and reduces acquisition of cell debris.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
(39 reference statements)
2
11
0
Order By: Relevance
“…Our study findings are comparable with other recent reports, demonstrating improved sensitivity of flow cytometric MRD assays with implementation of a pre-lysis technique (Flores-Montero et al, 2017;Kalina et al, 2012;Muccio et al, 2018;Theunissen et al, 2017). Despite concerns for the potential of additional wash steps to increase cell loss, and the limited data available regarding the impact of pre-lysis on antigen-antibody stability, our study demonstrated no compromise in antigen stability across three different disease panels, and more reliably achieved a higher sensitivity.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Our study findings are comparable with other recent reports, demonstrating improved sensitivity of flow cytometric MRD assays with implementation of a pre-lysis technique (Flores-Montero et al, 2017;Kalina et al, 2012;Muccio et al, 2018;Theunissen et al, 2017). Despite concerns for the potential of additional wash steps to increase cell loss, and the limited data available regarding the impact of pre-lysis on antigen-antibody stability, our study demonstrated no compromise in antigen stability across three different disease panels, and more reliably achieved a higher sensitivity.…”
Section: Discussionsupporting
confidence: 89%
“…Various methods currently available for MFC sample preparation are selected based on providing the best signal discrimination between populations, improving signal to noise ratio, minimization of nonspecific binding, auto-fluorescence, and antibody specificity (Tanqri et al, 2013;Wood, 2016). SLW protocols are widely adopted in the diagnostic setting, providing better signal discrimination (Johansson, Bloxham, Couzens, et al, 2014;Muccio et al, 2018). With novel sample preparation procedures, attaining a high number of events is a priority; however, clear distinctions between positive and negative populations remains essential.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations